Removal of chlorinated volatile organic compounds by fixed bed adsorption technique: Adsorption equilibrium and breakthrough analyses - Kalender, Mehmet; Akosman, Cevdet (Ars Docendi, 2015)
The adsorption equilibrium and dynamic breakthrough behaviour of chlorinated volatile organic compounds (CVOCs), namely chloroform and carbon tetrachloride, were experimentally investigated by using pelleted activated carbon in a fixed bed. The experimental studies were carried out at atmospheric pressure, the temperature of 313 K, the gas flow rate of 3 L/min and various inlet gas phase concentration of CVOCs (250-1250 ppmv). The experimental adsorption equilibrium isotherms were obtained and compared with four model equations (Freundlich, Langmuir, DRK and BET) existing in literature. It was observed that the Freundlich and Langmuir isotherm models were in agreement with the experimental data obtained. It was also observed that K-F and q(m) values of chloroform on the activated carbon used were greater than those values of carbon tetrachloride. The Yoon Nelson and deactivation models were used to describe the breakthrough curves of the CVOCs studied on the activated carbon by using the experimental data. It was found that the model results were in agreement with the experimental breakthrough curves.
Keywords: Air pollution; chlorinated volatile organic compounds; activated carbon; adsorption; fixed bed